Dynamics of Destruction of Two-dimensional Analog Models Discrete Environments with Different Organization of their Structural Compositions - Sheludchenko, B; Zabrodsky, P (Annals of Mathematics and Physics, 2024)
Based on the main phenomenological features of the Coulomb-Navier rheological body, several most characteristic simulated models of discrete environments with different structural compositions have been proposed. Mechanical testing of the specified simulator models allows for investigating the dynamics of deformation (restructuring of composition) of discrete (including loose) environments with varying organization (within a wide range) of their structural compositions. The main thermodynamic peculiarities of the deformation and destruction processes of discrete environment structures under different variations of external loading application schemes have been identified.